DSP based fuzzy and conventional overcurrent relay controller comparisons - Goh Y.L.; Ramasamy A.K.; Nagi F.H.; Zainul Abidin A.A. (2023)
Fuzzy logic control uses linguistic approach to solve complicated rules and ambiguous systems. This control strategy can be used to improve the overall performance of an overcurrent relay for power system protection compared to conventional relay. It is essential for a relay to work efficiently to trip the circuit breakers in the presence of faults and at the same time proficient to coordinate well with the networks to avoid mal-operation. There are two different types of fuzzy logic control strategies proposed for the relay, the Fuzzy Logic Controller (FLC) and Fuzzy Bang-Bang Controller (FBBC). The FBBC is the same as the conventional FLC except that the defuzzification method uses largest of maxima (LOM). Comparisons between the fuzzy controllers and conventional relay are based on IEC 255-3 standard. These relays are implemented on a DSP TMS320F2812 and their performance is evaluated which is based on operation time, DSP's execution time and grading margin. The results obtained show a significant performance improvement compared to conventional relay. 2013 Elsevier Ltd. All rights reserved.